2012
DOI: 10.1016/j.ijpe.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple part-type scheduling in flexible robotic cells

Abstract: a b s t r a c tThis paper considers the scheduling problem arising in two-machine manufacturing cells which repeatedly produce a set of multiple part-types, and where transportation of the parts between the machines is performed by a robot. The cycle time of the cell depends on the robot move sequence as well as the processing times of the parts on the machines. For highly flexible CNC machines, the processing times can be adjusted. To this end, this study tries to find the robot move sequence as well as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Considering di erent aspects including machine grouping control, Virtual Manufacturing Cells (VMCs), owline manufacturing cell, group layout design model, etc., CSP has been studied by some researchers: Solimanpur et al [27], Logendran et al [28], Venkataramanaiah [29], Tavakkoli-Moghaddam et al [30], Lin et al [31], Shirazi et al [32], Kesen et al [33], Lin et al 2011 [34], Kia et al [35], Batur et al [36], Izui et al [37], Boutsinas [38], and Fazlollahtabar and Jalali Naini [39]. Later, Zeng et al [40] studied the problem of parts scheduling in multi-job shop cells by considering exceptional parts that need to visit machines in di erent cells and be transferred by robot with the objective of minimizing the make-span.…”
Section: Csp Studiesmentioning
confidence: 99%
“…Considering di erent aspects including machine grouping control, Virtual Manufacturing Cells (VMCs), owline manufacturing cell, group layout design model, etc., CSP has been studied by some researchers: Solimanpur et al [27], Logendran et al [28], Venkataramanaiah [29], Tavakkoli-Moghaddam et al [30], Lin et al [31], Shirazi et al [32], Kesen et al [33], Lin et al 2011 [34], Kia et al [35], Batur et al [36], Izui et al [37], Boutsinas [38], and Fazlollahtabar and Jalali Naini [39]. Later, Zeng et al [40] studied the problem of parts scheduling in multi-job shop cells by considering exceptional parts that need to visit machines in di erent cells and be transferred by robot with the objective of minimizing the make-span.…”
Section: Csp Studiesmentioning
confidence: 99%
“…Yildiz et al [28] studied a robot-centered cell consisting of multiple CNC machines producing identical parts. Batur et al [5] suggested a A C C E P T E D M A N U S C R I P T 4 solution to the scheduling problem in a two-machine manufacturing cell that repeatedly produces a set of parts of multiple types, with a robot transporting the parts between machines. Che et al [29] also considered the cyclic scheduling of a no-wait re-entrant robotic flow shop with multiple robots for material handling.…”
Section: Literature Surveymentioning
confidence: 99%
“…A major application of robots in manufacturing involves the loading and unloading of production machines in manufacturing cells. A robot in such a cell performs repeated sequences of pick-up, movement, loading, unloading and dropping operations, and thus, the performance of the cell strongly depends on the sequence of robotic activities and on the sequence of the different parts produced in the cell [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As a basic component of a flexible manufacturing system, flexible material handling is crucial in achieving manufacturing flexibility (Didem Batur, 2012;D'Souza and Williams, 2000;Koste & Malhotra, 1999;Sawhney, 2006).…”
Section: Materials Handling Flexibilitymentioning
confidence: 99%